Determination of Optimum pH and Contact Time from the Adsorption Process of Cu(II) Ions by Corn Cob (Zea mays) Biomass - Riska T. Windiastuti; Tri Santoso (Universitas Tadulako, 2020)
The use of Cu in daily life and industry can produce toxic waste, both for the human body and the environment. This study aimed to determine the optimum pH value and contact time, and the maximum capacity of the adsorption process of Cu(II) ions by corn cob biomass. The optimum pH and contact time were determined based on the adsorption graph of the adsorbent obtained from the optimization of pH and time, while the maximum adsorption capacity was determined using the Langmuir adsorption isotherm equation. The results showed that the optimum pH adsorption of Cu(II) ions by corn cob absorbent occurred at pH 7 with the absorption of 98.34%. Optimum contact time occurred at the 60th minute with the percentage of copper absorbed was 96.37%. Besides, the maximum capacity adsorption of corn cobs toward Cu(II) ions was 2.416 mg/g. This study concluded that corn cobs can be used as an adsorbent of Cu(II) ions.